ANALISIS NILAI INTERFERENSI TERHADAP PERFORMANCE ACCESS POINT EDIMAX BR-6428NS V2 N300 BERBASIS QUALITY OF SERVICE (QoS) - ., Rangga Eko Widiantoro (Faculty of Engineering, Universitas Tanjungpura, 2019)
Interference is thought to have an effect on performance which results in a decrease in the performance of the network of wirelees , who are the hardest disturber in the world of wifi. Interference is a fellow radio wave signal that operates at the same frequency, interval and area , as a result the device client will experience an error when translating the same information code . This study aims to find out how to use a good access point , to avoid interference that can cause a decrease in performance and level of quality at the performance of the access point . QoS parameter measurement uses a speedtest to measure internet access speed, Axence NetTools Pro 4.0 software for measuring delay , packet loss and throughput and NetStumbler 0.4.0 software for measuring signal strength , noise and SNR (Signal to Noise Ratio) . The results of testing the average QoS parameters in the researcher's home area for internet access speed using the same frequency, namely the download value of 10.10 MB p and the upload value of 1.31 MB ps. These values can be said to be very good. The average yield of 106.25 ms delay measurement (TIPHON: Very Good and ITU-T: Good), use values jitter as big as 105.40 ms (TIPHON: Moderate), packet loss value of 2.87 % (TIPHON: Bagus and ITU-T : Good ) and a throughput value of 392.125 Kbps (TIPHON: Enough). While the results of testing the average QoS parameters in the researcher's home area for internet access speeds that use adjacent frequencies are download values of 9.95 MBps and upload values of 1.38 MBps, these values can be said to be very good. The average yield of 62.87 ms delay measurement (TIPHON: Very Good and ITU-T: Good), use values jitter as big as 62.35 ms (TIPHON: Good), the value of packet loss amounted to 3.375% (TIPHON: Nice and ITU-T: Good) and the throughput of 479.75 Kbps (TIPHON: Enough). Factors that can cause the value of QoS to decrease are network that is not stable, increasing distance when making measurements that can affect the quality of the network because the farther the distance to be measured, the quality of the signal obtained decreases.